Knowledge Networks: Innovation Through Communities of Practice - Hildreth, Paul; Kimble, Chris (IGI Global, 2003)
Knowledge Networks: Innovations Through Communities of Practice draws on the experience of people who have worked with CoPs in the real worl d and to present their combined wisdom in a form that is accessible to a wide audience. CoPs are examined from a practical, rather than a pu rely academic point of view. The book also examines the benefits that CoPs can bring to an organization, provides a number of case studies, lessons learned and sets of guidelines. It also looks at virtual CoPs and to the future by asking 'what next?' This book is a resource for a ll people who work with CoPs - both in academia and in the real world.